Concepts dictionary of agricultural sciences - Gupta, L.C.; Gupta, S.K. (New Dehli : Concept Publisher Company, 1992)
Agriculture being a multidisciplinary approach, specialists in one discipline often come across words with which they are not familiar. This definitional dictionary contains definitions of terms commonly encountered by the researchers, planners and common man related to the field of agriculture. The scope of the book has been broadened by including terms from varying disciplines such as agronomy, agricultural engineering, botany, breeding, chemistry, climatology, entomology, genetics, geology, plant physiology, social sciences and soil science. The words could be easily located as these have been arranged alphabetically. This compilation should satisfy users as terms very commonly encountered have been listed.
Keywords: Agriculture -- Dictionaries; Agriculture